For the right to be and to remain free: (In)justice and resistance to slavery (Taubaté, 1887) - Albano, Nícollas Lopes Cardozo; Ribeiro, Suzana Lopes Salgado (Cordis: Revista Eletrônica de História Social da Cidade, 2025)
This article results from research with historical documents and aims to trace the main elements of Vicência’s narrative, a former enslaved woman that filed a lawsuit to reconquer her manumission. Freed in 1886, Vicência was arrested and reconsidered as an enslaved woman in 1887. The primary source of this study is part of the collection of Arquivo Histórico Municipal “Felix Guisard Filho”, and it cooperates with the constitution of a Micro-History-based slavery historiography in Taubaté. Therefore, the manuscript’s analysis was elaborated with the purpose of comprehending the context of Vicência’s lawsuit, so after that would be possible to reflect upon black anti-slavery resistance actions, and about the colonialist structures present at 19th century Taubaté. It was concluded that this document shows, beyond the feminine agency against the system, a counterattack of the coloniality of power, that strengthened racism, negligency and subservience against black bodies in that context.